2015
DOI: 10.1007/s40095-015-0166-0
|View full text |Cite
|
Sign up to set email alerts
|

Exergoeconomic optimization of an ammonia–water hybrid absorption–compression heat pump for heat supply in a spray-drying facility

Abstract: Spray-drying facilities are among the most energy intensive industrial processes. Using a heat pump to recover waste heat and replace gas combustion has the potential to attain both economic and emissions savings. In the case examined a drying gas of ambient air is heated to 200°C yielding a heat load of 6.1 MW. The exhaust air from the drying process is 80°C. The implementation of an ammonia-water hybrid absorption-compression heat pump to partly cover the heat load is investigated. A thermodynamic analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…The exergetic efficiency of the total installation was calculated as seen in Eq. (20). Here the entire heat load supplied to the DH stream was accounted as the exergetic product, while the entire heat load supplied from the GT stream plus the power supplied to the two HPs was accounted as the exergetic fuel.…”
Section: Generic Energy and Exergy Model Of The Geothermal Installationmentioning
confidence: 99%
See 1 more Smart Citation
“…The exergetic efficiency of the total installation was calculated as seen in Eq. (20). Here the entire heat load supplied to the DH stream was accounted as the exergetic product, while the entire heat load supplied from the GT stream plus the power supplied to the two HPs was accounted as the exergetic fuel.…”
Section: Generic Energy and Exergy Model Of The Geothermal Installationmentioning
confidence: 99%
“…With the current pressure level of commercially available components the HACHP is capable of delivering significantly higher temperatures than the conventional vapour compression heat pump (VCHP), however this requires the correct combination of ammonia mass fraction and circulation ratio to be identified [19]. The HACHP has been shown to provide a good return on investment as well as a significant reduction of CO 2 emission when applied for industrial process heating, in e.g spray drying facilities [20].…”
Section: Introductionmentioning
confidence: 99%
“…Jensen et al [12] numerically investigated the influences of ammonia mass fraction and liquid circulation ratio on the system constrains, results showed that the maximum heat supply temperature was 111 °C when using standard refrigeration components without modifying the compressor (28 bar limitation); for high pressure ammonia based components, the maximum supply temperature can be 129 °C (50 bar limitation) and for transcritical CO2 based components, the maximum supply temperature can be 147 °C (140 bar limitation). The authors [13] i.e. electricity and/or waste heat, depending on their availabilities; secondly, more waste heat can be recovered as the system required thermal inputs of both generator and evaporator while the required electricity can be less.…”
Section: Frmentioning
confidence: 99%
“…An environmentally friendly refrigeration system is one of the solutions offered by researchers as an efficient and high-performance system (Curtis et al 2005;Omer 2008). This system is considered capable of reducing primary energy consumption and offering an efficient equipment (Chua et al 2010;Jensen et al 2015). Vapor compression refrigeration and absorption systems are two technologies that have been developed recently (Curtis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%